THE SOLUTIONS OF BLOCKCHAIN TECHNOLOGY IN ACCOUNTING PERSPECTIVE: A SYSTEMATIC LITERATURE REVIEW - Heni Suryanti; Dhieka Avrilia Lantana; Syamsudin; Kumba Digdowiseiso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The emergence of blockchain technology has the potential to revolutionize the accounting field with substantial consequences. These challenges encompass issues in traditional accounting practices, such as the potential for fraudulent activities, human mistakes, and manipulation of data. The objective of this study is to assess the potential of blockchain technology as a means to address these issues from an accounting standpoint. The employed approach is Systematic Literature Review (SLR), which entails a thorough exploration and examination of relevant literature. The findings of this systematic literature review (SLR) demonstrate that the utilization of blockchain technology in the field of accounting holds the promise of enhancing security, transparency, and efficiency in financial record-keeping and reporting. Blockchain technology also facilitates the implementation of triple-entry based accounting principles and real-time reporting, thereby enhancing financial performance. Furthermore, blockchain provides a robust level of data security via advanced encryption technology. Despite the existing technical and regulatory obstacles, the advantages presented by blockchain technology in the field of accounting are substantial and have the capacity to revolutionize accounting methodologies entirely. The study concludes that blockchain technology holds significant potential in addressing various challenges in accounting, enhancing the accuracy of financial information, and reinforcing integrity throughout the accounting process.